2014
DOI: 10.1186/s12912-014-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Are care workers appropriate mentors for nursing students in residential aged care?

Abstract: BackgroundThe aged care sector is increasingly dominated by a less-qualified workforce at a time of increasing prevalence of complex health concerns, such as dementia. An Australian program to develop teaching aged care facilities is being undertaken to build the sector’s capacity and provide nursing students with positive experiences of engaging with vulnerable clients. This research aimed to examine care staff potential to facilitate nursing student engagement with clinically relevant knowledge in the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 40 publications
3
50
0
Order By: Relevance
“…Globally, work in aged care settings is often characterised by low pay and status, manual labour, shift work, high staff turnover and limited opportunities for professional development (Annear et al 2014;Hugo 2007;Ministry of Health, Labour & Welfare 2016). There are also persistent hierarchies within the health professions of many developed countries, which often unfairly subordinate and devalue nursing and caring roles within the health care sector and wider society (Walker & Holmes 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, work in aged care settings is often characterised by low pay and status, manual labour, shift work, high staff turnover and limited opportunities for professional development (Annear et al 2014;Hugo 2007;Ministry of Health, Labour & Welfare 2016). There are also persistent hierarchies within the health professions of many developed countries, which often unfairly subordinate and devalue nursing and caring roles within the health care sector and wider society (Walker & Holmes 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the community setting in Ireland, HSWs work within the social care division, not primary care (HSE, 2015). This division could leave the HSWs feeling that they are disconnected rather than being part of an integrated team, leading to feelings of being undervalued (Annear et al, 2014). As their level of training is seen to be of a lower standard, the risk remains that due respect is not shown to them by other healthcare workers.…”
Section: Valuesmentioning
confidence: 99%
“…Findings within the literature suggest that the HSW's caring role and tasks performed vary depending on the country or clinical area in which they are employed. This leads to role confusion (Annersten-Gershater , Annear et al, 2014and Hewko et al, 2015. Swedberg et al (2013) demonstrated that patient safeguarding and quality of care given could not be guaranteed or uniform, given the confusion regarding the exact nature of the HSW role.…”
Section: Role Developmentmentioning
confidence: 99%
See 2 more Smart Citations